Контроль працездатності сушильної установки у складі когенераційної системи - Чайковська, Євгенія Євстафіївна (НТУ "ХПІ", 2016)
Контроль працездатності сушильної установки з використанням аналітичної оцінки зміни вологовмісту повітря в сушильній камері при вимірюванні температури повітря на вході в теплообмінник підігріву повітря дозволяє приймати рішення на зміну витрату повітря, що нагрівається, на основі зміни частоти обертання електродвигуна повітряного вентилятора. Узгодження температурного та аеродинамічного режимів сушки деревини надає можливість, наприклад, при виробництві 5,8 тис. т пелет з деревини в рік здобути грошову економію при використанні пелетного палива до 40% та знизити собівартість виробництва енергії у складі когенераційної системи в межах 20–30 %.

The paper presents the architecture of a cogeneration system, the foundation of which is the dynamic subsystem. It includes a cogeneration plant, drying plant, air heating heat exchanger, an air fan. Other units are units of discharge, charge, assessment of functional efficiency, which are consistent with the dynamic interaction subsystem. It is proposed an analytical evaluation of changes in the moisture content of the air in the drying chamber at an air temperature measured at the outlet of the drying chamber. Set functioning levels of dryer air temperature change at the inlet of the heat exchanger and heating the air leaving the heat exchanger which corresponds to a change of the equilibrium moisture content of wood in the drying chamber. The air flow entering the air-heating heat exchanger which corresponds to the level functioning the dryer is defined. The valid values change in the moisture content of the air in the drying chamber obtained. The block diagram of logical modeling dryer developed. The functional information is obtained. It allows to change the air flow entering the heat exchanger preheating the air in measuring air temperature at the outlet of the drying chamber. Changing the air blower motor speed for changes in air flow provides thermal drying treatment in the drying chamber. Coordination of temperature and aerodynamic regimes of drying wood allows, for example, the production of 5.8 thousand tons of wood pellets per year to provide 860 apartments measuring 120 m2 pellet fuel that given the frequency regulation on electric air fan drying materials, provides gain saving money using pellet fuel for heating and hot water to 40% and reduce the cost of power generation and heat within 20%-30% in in the conditions of the cogeneration system.
Control working ability of the drying plant in the composition of the cogeneration system
Keywords: когенераційна установка; пелетне паливо; вологовміст; cogeneration plant; pellet fuel; drying plant; moisture content